Analisis determinan loyalitas pengunjung di perpustakaan kota x - Agustina, Anis; Budiwibowo, Satrijo; Yusdita, Elana Era (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2020)
This study aims to analyze visitor loyalty based on service quality and visitor satisfaction in the Library of City X. The approach of this study is descriptive qualitative. Data collection techniques using observation, interviews and documentation on visitors and library employees. The results show that the loyalty of visitors in Library X is quite good, but the quality of service and satisfaction of visitors is not yet in accordance with the visitors expectation. The Library and Archives Office of City X needs to improve the quality of services and facilities that will make visitors loyal and satisfied.